PENGARUH ASPEK SUMBERDAYA MANUSIA DANLINGKUNGAN KERJA TERHADAP KINERJA GURU DALAMPENERAPAN SISTEM MANAJEMEN MUTU ISO 9001:2008 DISMKN 2 NGANJUK - DEBI IRSYADA, BURHANUDDIN (Jurnal Pendidikan Tata Niaga (JPTN), 2013)
The results showed that the simultaneous human resources and working environment affect the performance of teachers/educators either simultaneously or partial. It can be seen from the Adjusted R Square of 0,462 effect simultaneously between human resources and a work environment on performance of teachers. While the magnitude of the partial influence of human resources toward teacher performance is as big as 0,573 or 57,3%. While the magnitude of the partial influence of work environment on performance of teachers amounted to 0,528 or 52,8%. This shows that human resources are a bigger influence on partial has on performance. Keywords: human resources labour and environmental performance